A case report of Hymenolepis diminuta infection in a Malaysian child - Rohela, M.; Ngui, R.; Lim, Y. A. L.; Kalaichelvan, B.; Wan Hafiz, W. I.; Mohd Redzuan, A. N. (Malaysian Society of Parasitology and Tropical Medicine, 2012)
We report a case of Hymenolepis diminuta infection in a 2-year-old Malaysian child. This case was initially reported as 'normal' after the examination of proglottids shed from the anus of the child at a private laboratory on two occasions. The putative proglottids shed was then referred to the Parasite Southeast Asia Diagnostic (Para:SEAD) Laboratory, Department of Parasitology, Faculty of Medicine, University of Malaya for further examination. Microscopic examination confirmed that the child was infected with H. diminuta based on the characteristic eggs found in the proglottids. She was treated with a single dose praziquantel (20 mg/kg of body weight) and recovered well.